A mechanically strong and tough anion exchange membrane engineered with non-covalent modalities. Issue 91 (3rd November 2017) - Wang, Xiaojuan; Wang, Ping; Sun, Yiyan; Wang, Jinlei; Fang, Huagao; Yang, Shanzhong; Wei, Haibing; Ding, Yunsheng
Abstract : A mechanically robust and tough anion exchange membrane was constructed using the strategy of supramolecular modalities. Abstract : A mechanically robust and tough anion exchange membrane was constructed using the strategy of supramolecular modalities. After introducing a secondary amide as a hydrogen-bonding crosslinking motif into the side chain of the PPO backbone, the membrane exhibits high mechanical strength and excellent flexibility (101% elongation at break), as well as suppressed water uptake, enhanced thermal stability and good fuel cell performances.